Philanthropic nation branding, ideology, and accumulation: insights from the Canadian context - Saifer, Adam (Journal of business ethics, 2021)
In this article, I make the case for—and begin the task of—examining the role of nation branding in the philanthropic sector. Using a series of cases drawn from Canadian organized philanthropy, I explore the ideological work that philanthropic nation branding does, as well as the social and political implications of this phenomenon. I bring critical theories of nation and national identity together with Marxian-inspired theories of capitalism—particularly those that foreground the racial and colonial dimensions of capital accumulation—to illuminate the nationally embedded contradictions at the core of organized philanthropy in Canada. Specifically, I focus on how racialized and colonial discourses of the nation are mobilized in philanthropic nation branding in ways that elevate and legitimize organized philanthropy as a contradiction-free mechanism for addressing racial and colonial inequities in Canada. In doing so, philanthropic nation branding obscures the explicitly racial and colonial processes of accumulation that produce the philanthropic wealth powering much of the sector, thereby reinforcing an ahistorical Canadian nation brand. Through this analysis, I illustrate the importance of centering race and national identity in critical work on the political economy of philanthropy, organizational branding, and the ethics of philanthropy as a social policy mechanism in Canada, as well as other national contexts.